Negative impact of abattoir activities and management in residential neighbourhoods in Kuala Terengganu, Malaysia - Auwalu, Abdullahi; Norizhar, Kadarman; Azmi, Hassan; Ibrahim, Sulaiman Madob (2015)
Poor management of abattoirs results in air and water pollution especially resident’s in their close proximity. The objevtive of the study was to investigate the effect of poor management of abattoirs on the quality of life and health of residents in their vicinity. A cross sectional survey was conducted within two month period. Fifty six residents of buildings located approximately five kilometers radius to the abattoir were randomly selected for interview using questionnaire. Among the 56 residents interviewed, 20 (35.7%) were sicked. Almost half (33.9%) of the residents suspected the sickness to be related to abattoir hazards. The prevalence of diseases and symptoms experianced by the residents were typhoid fever (14.4%), Diarhoea (12.5%), Coughing (10.7%), Asthma (8.9%), Foot and Mouth Disease (7.1%) and Dengue (3.6%). The main associated factors of abattoir activities on residents ‘s health were contamination of air with pollutants (odds ratio,15.52; 95% confidence interval, 3.62-10.52), water contamination (11.44; 3.17, 12.28), gutters and drainages blockage (6.35; 1.26, 9.99) and prevention of children from outdoor activities (4.65; 1.33, 16.31). There was also reported case of food poisoning among the residents. Abattoir activities has direct and indirect negative effect on residents health who are in close proximity.